Effects of toroidal rotation on electron heat transport via changes in inertial force and impurity density. (7th March 2017) - Narita, E; Honda, M; Yoshida, M; Hayashi, N; Urano, H; Ide, S
Abstract: Two types of JT-60U discharges are studied with an emphasis on toroidal rotation: in one discharge, which is characterized by the existence of an internal transport barrier (ITB), electron heat transport in the core region is affected by the toroidal rotation direction, while in the other discharge, which is a conventional H-mode plasma without an ITB, the clear correlation between the toroidal rotation direction and electron heat transport is not observed. In both discharges, the impurity density is also found to vary together with the rotation velocity profile. With a flux-tube gyrokinetic code, we have found that the effects of the changes in the rotation velocity profile and the impurity density on electron heat transport are different between these discharges. Including the effects explains the tendency observed in the experiments. First, regarding the rotation velocity profile, which influences heat transport through the inertial force, the dependence of heat transport on the rotation direction changes, according to the gradient of the rotation velocity. Next, an increase in the impurity density stabilizes the ion temperature gradient mode, but can destabilize the trapped electron mode. Therefore, it is found that the difference in the impact of the impurity density on electron heat transport in these discharges can be attributed to the difference in the dominant instability.